Adaptive strategies of overwintering adults: Reproductive diapause and mating behavior in a grasshopper, Stenocatantops splendens (Orthoptera: Catantopidae). (24th May 2012) - Zhu, Dao‐Hong; Cui, Shuang‐Shuang; Fan, Yong‐Sheng; Liu, Zhiwei
<x xml:space="preserve">Abstract</x> Abstract To understand the adaptive strategies of the overwintering adults of Stenocatantops splendens, the mechanism of maintenance and termination of the reproductive diapause, the variation in mortality between overwintering females and males, and the mating strategy of the males were investigated. The results indicated that the adult reproductive diapause in natural conditions was mainly regulated by photoperiod in the fall – long photoperiods promoted reproductive development and short photoperiods maintained reproductive diapause, and the sensitivity of the overwintering adults to photoperiod was over before the end of the winter. When transferred from natural conditions to controlled laboratory conditions on dates from September through February, pre‐oviposition became increasingly shorter with increasingly deferred transfer dates regardless of photoperiod conditions. The adults treated with low temperature for 30 days in September through November had significantly shorter pre‐oviposition, suggesting that low temperatures in winter had an important role in the termination of reproductive diapause. The female had a significantly lower supercooling point than the male, which was related to their lower mortality after winter. In addition, observations of wild populations of the species indicated that mating behavior prior to winter and the duration of pre‐mating period were not affected by photoperiod; mating and sperm transfer were mostly completed by November. Compared with females only mating before winter, females mating in the spring had shorter life span, longer pre‐oviposition, lower hatching rate and laid fewer egg pods while showing no significant difference with regard to ovipositional interval, per pod number of eggs and nymph dry weight.